Experiences among parents caring for children with juvenile idiopathic arthritis at a tertiary referral hospital in Kenya - Silim, Hassan; Wamithi, Susan; Riang’a, Roselyter M.; Migowa, Angela (Frontiers in Pediatrics, 2025)
BackgroundJuvenile idiopathic arthritis (JIA) is the most common rheumatic disease in childhood. Despite the availability of effective treatment strategies such as disease-modifying antirheumatic drugs (DMARDs), JIA is reported to have a negative impact on the quality of life of the patients and their caregivers. Ascertaining the perceptions of the parents will help facilitate more effective management strategies and improve outcomes for these patients. This study aimed to ascertain parental experiences and perceptions of caring for children with juvenile idiopathic arthritis (JIA).MethodsThis was a single-center facility-based qualitative study. An in-depth interview guide was used to collect data from parents (n = 12) of children with juvenile idiopathic arthritis aged between 0 and 16 years attending the pediatric rheumatology clinic at a tertiary referral hospital in Kenya. Interviews were audio-recorded, transcribed verbatim, and thematically analyzed using the MAXQDA22.6 program.ResultsA total of 12 parents participated in the study: 9 mothers and 3 fathers aged from 35 to 47 years. All parents were from middle- and low-income families. The study revealed parental experiences and perceptions in eight key domains: medical-related challenges, emotional aspects, coping mechanisms to deal with emotional burden, financial challenges, social challenges, healthcare personnel-associated experiences, disruption of work, and absenteeism by parents. Parents faced challenges in looking for resources and support to cope with the difficult moments of caring for their sick children. These challenges not only affected the parents but also affected the relationships in their entire families, including siblings, relatives, and their relationships among friends.ConclusionThe findings in this study highlight the challenges experienced by parents caring for children with JIA. Health workers need to be vigilant to the plight guardians go through and create support avenues to help them navigate the challenges they experience. There is a need for proper assessment of the physical and psychosocial well-being of parents and their families so that appropriate resources can be provided in promoting holistic patient-centered care.